Contribution of Co-operative in Nepalese Economy: A Case Study of Paropakar Saving and Credit Cooperative Ltd - Devkota, Shiva Prasad (Madhyabindu Journal, 2021)
This study "Contribution of Co-operative in Nepalese Economy" (A Case Study of Paropakar Saving and Credit Cooperative Ltd) is an attempt to explore the overall status and activities, credit, and the investment pattern in the business sector of Paropakar saving Credit Cooperative Ltd, and also find out the types of credit provided to the team members of saving and Cooperative. This study is based on both qualitative and quantitative research designs. It employed historical, analytical, and descriptive research exclusively based on secondary data. Annual report of Paropakar Saccos to achieve the research objective. I have edited, coded, and tabulated the accumulated data and presented it in the form of a graph, table, chart, and trend line. The finding of the study shows that there is a high investment in NEFSCUN in comparison to other sectors. It provides a huge amount of business loans to the businessman for the creation of economic activities which ultimately helps to achieve the economic goal of the cooperative. It also reflects that the investment pattern is low in comparison to the credit patterns in the Saccos. The cooperative should invest the money in the productive sector which helps to uplift the living standard of poor, marginalized, vulnerable, women, disabled, and economically disadvantaged people and high rate of economic growth. Moreover, by providing various loans, Co-operative helps to attract the youth in the agriculture sector, and also helps to produced small scale to the higher-level businessman.